ANALYSIS OF NORTH SULAWESI SEA WATER MASS COMPOSITION AND ITS HEAT CONTENT IN 1995 - 2015 - Lazuardi Ramadhan, Fauzan
The North Sulawesi Sea is the entrance gate of Indonesian Troughflow (ITF) which will be directly affected by the phenomenon occurring in the Pacific Ocean. This study aims to determine the composition of the water mass and each of its heat content in the North Sulawesi Seas as part of ITF. The data used in this study is salinity and temperature data derived from the HYbrid Coordinate Ocean Model (HYCOM) reanalysis model with a resolution of 1/12°. Optimum Multiparameter (OMP) is used to calculate the percentage of mixing contributions from each water mass in the study area. The North Pacific Subtropical Water (NPSW) water mass has a maximum contribution at a depth of < 100 m with a contribution of mixing > 80%, mixture of NPSW, South Pacific Subtropical Water (SPSW), North Pacific Equatorial Water (NPEW), and North Pacific Intermediate Water (NPIW) at depth between 100 - 300 m are 10% - 80 %, 0% - 25%, 10% - 50%, and 10% - 40%, respectively. A mixture of NPEW and NPIW at depth between 300-500 m has contributed to mixing between 20% - 80% and 50% - 70% , NPIW dominated depth between 500-600 m with a contribution of > 80%, Antartic Intermediate Water (AAIW) at depth between 600-1500 m has a contribution of > 80%, Antartic Bottom Water (AABW) influenced depth > 2500 m with mixing contributions > 70%. A mixture of AAIW and AABW water masses is found at depth between 1500 - 2500 m with a contribution between 10% - 60% for both. Mass residual conservation <1,5%. This indicates that there is still a mixture of another water mass. The water mass heat content is calculated with the two different temperature systems for depth. In the period of 1995-2015 the heat content of AABW water mass contributed 26,46%, AAIW was 52,3%, NPEW was 10,1%, NPIW was 10,26%, and NPSW was 0,86% of the total heat content in the North Sulawesi Seas, the contribution is strongly influenced by variations in temperature to depth. The water mass heat content in the mixed and deep layer will decrease (increase) when the La-Niña (El-Niño), while in the thermocline layer will decrease (increase) when the El-Niño (La-Niña) phenomenon.